2014
DOI: 10.1186/bf03351670
|View full text |Cite
|
Sign up to set email alerts
|

Spectral power of low-latitude Pi 2 pulsations at the 210° magnetic meridian stations and plasmaspheric cavity resonances

Abstract: Pi 2 pulsations at low latitudes are examined with magnetic fields data at the 210• magnetic meridian (MM) stations in 1991. Due to high degree of coherence over most latitudes, 68 low-latitude Pi 2 events at the 210• MM stations are identified with reference to same waveforms on the magnetogram at Lunping (189.5• MM, L = 1.06). With spectral power analysis, the ratio of the first four harmonic frequencies of low-latitude Pi 2 pulsations is about 1 : (1.7 ± 0.1) : (2.3 ± 0.1) : (2.9 ± 0.1). By using a box mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
8
29
1
Order By: Relevance
“…By contrast, the waveforms of Pi2s at mid-L and low L stations are almost in the same phase as those along the East Coast except for PINA (L = 4.02) and RMUS (L = 2.91) having a shorter period for the F1 burst only. These are consistent with the observational results by Cheng et al (2009a), that THEMIS Pi2s have the characteristics of the fundamental magnetospheric cavity mode resonances with 180 • of phase change from high to low latitude across the plasmapause (see Lin et al, 1991;Cheng et al, 1998Cheng et al, , 2000. Hence, consecutive Pi2 bursts for this event can be a fast magnetospheric cavity mode.…”
Section: Discussionsupporting
confidence: 80%
“…By contrast, the waveforms of Pi2s at mid-L and low L stations are almost in the same phase as those along the East Coast except for PINA (L = 4.02) and RMUS (L = 2.91) having a shorter period for the F1 burst only. These are consistent with the observational results by Cheng et al (2009a), that THEMIS Pi2s have the characteristics of the fundamental magnetospheric cavity mode resonances with 180 • of phase change from high to low latitude across the plasmapause (see Lin et al, 1991;Cheng et al, 1998Cheng et al, , 2000. Hence, consecutive Pi2 bursts for this event can be a fast magnetospheric cavity mode.…”
Section: Discussionsupporting
confidence: 80%
“…By analyzing the LT dependence of the dominant frequency for the three kinds of data sets, we confirmed that the dominant frequency of the H component are lower on the dusk side than that on the dawn side, and the dominant frequencies have a maximum value at To understand the LT dependence of the frequency of Pi2 waves, we need to consider the following two aspects. Firstly, in recent years, many researchers, such as Sutcliffe and Yumoto (1989), Takahashi et al (1995Takahashi et al ( , 2003, Lee (1996), Cheng et al (2000) and Denton et al (2002), suggested that a cavity resonance mode of the plasmasphere is a reasonable mechanism for the generation of Pi2 pulsations within the plasmapause at low latitudes. Nosé et al (2003) found that the plasmaspheric cavity mode resonance can be established even on the morning side.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As for defining the onset and duration of Pi2s, different criteria have been used by different authors (Takahashi et al, 1995;Cheng et al, 2000;Kosaka et al, 2002). In this paper, based on the length of the data, we adopted three types of data sets which are called "10-minute data set", "5-minute data set" and "trailing-5-minute data set", respectively.…”
Section: Data Set and Event Selectionmentioning
confidence: 99%
“…The latitudinal profiles of Pi 2 amplitudes and phase relations obtained at the CPMN stations in the STEP period imply that Pi 2 pulsations observed on the ground consist of different mode oscillations (see Yumoto et al, 1994;Yumoto and the 210 • MM Magnetic Observation Group, 1995;Osaki et al, 1996;Shinohara et al, 1997;Li et al, 1998a;Cheng et al, 2000;Li et al, 2000;Uozumi et al, 2000;Solovyev et al, 2000). Recently.…”
Section: Global Characteristics Of Pi 2smentioning
confidence: 99%